2007
DOI: 10.1177/1052562905282883
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Resource Planning Software in the Human Resource Classroom

Abstract: The relatively recent development of comprehensive human resource information systems (HRIS) software has led to a large demand for technologically literate human resource (HR) professionals. For the college student who is about to begin the search for that first postcollege job, the need to develop technology literacy is even more necessary. To meet this technology need, many business schools have started to think about or have begun to incorporate more advanced technology such as enterprise resource planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This is not to say that HR educators do not try to make the classes lively and interactive. On the contrary, HR educators put a great deal of effort into making HR alive and providing immersive and experiential learning for students, using exercises (Renard, 2008), cases (Manisaligil & Bilimoria, 2016), movies (Bumpus, 2000), simulations (Bedell et al, 2007; North-Samardzic & de Witt, 2019) and full-blown service-learning projects (Madsen & Turnbull, 2006). However, the challenge is that while these techniques improve the process element of teaching HR, they fail to fully address the gap in the course’s content element.…”
Section: The Current State Of the Undergraduate Introductory Hr Coursementioning
confidence: 99%
“…This is not to say that HR educators do not try to make the classes lively and interactive. On the contrary, HR educators put a great deal of effort into making HR alive and providing immersive and experiential learning for students, using exercises (Renard, 2008), cases (Manisaligil & Bilimoria, 2016), movies (Bumpus, 2000), simulations (Bedell et al, 2007; North-Samardzic & de Witt, 2019) and full-blown service-learning projects (Madsen & Turnbull, 2006). However, the challenge is that while these techniques improve the process element of teaching HR, they fail to fully address the gap in the course’s content element.…”
Section: The Current State Of the Undergraduate Introductory Hr Coursementioning
confidence: 99%
“…They also found that applying HRIS tools to understanding the traditional, functional areas of HRM would be most beneficial in preparing students for careers in HRM. Bedell et al (2007) examined the need for integrating enterprise resource planning software into HRM courses. This exploratory case study found that industry thought such education was worthwhile, and that faculty were receptive to such software, as long as the time invested in learning and implementing the software achieved a higher payoff in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%